The economy of the American people : progress, problems, prospects - Colm, Gerhard; Geiger, Theodore (Washington, D.C. : National Planning Association, 1961)
The volume provides background facts and analysis for policy statements on the US economy. It provides an analysis of the nature and prospect of the American economic system, how private enterprise economy have been able to achieve such high productivity and living standards.
Includes bibliographical footnotes.
kjo 17/01/2019
Loans
Keywords: Economics; United States